Consciência fonológica no biletramento português/inglês na educação bilíngue: uma proposta didática - Molina, Carolina Batista (2023)
In this study, we aim to explore and discuss Phonological Awareness and its benefits regarding the development of English as an additional language, as well as propose a series of prototype activities, based on the complexity of languages. Using a bibliographic research methodology, we present a literature review about language and its development in humans; the child and language development, assuming the conception of language as a complex system; bilingualism and biliteracy, and bilingual education in Brazil. We also review the uses of Phonological Awareness in the first language, as well as in the additional language, so that our arguments can become theoretical bases for the link between the literature review and the creation of pedagogical proposals such as prototype activities, hosted on the Internet, that deal with the development of Phonological Awareness. We observed that discussions about the teaching and learning of English as an additional language in the context of bilingual education in Brazil have expanded in recent years. However, studies on specific aspects of the development process of this additional language, specifically on Phonological Awareness skills, are still scarce. Thus, in the present study, we approach language and its development as parts of a complex adaptive system and then discuss theoretical and practical issues related to children's development of English Phonological Awareness skills in a bilingual education context. Based on this discussion, we propose a set of activities that aim to improve the Phonological Awareness skills of Brazilian Portuguese-speaking children. These activities are designed for the eight to ten-year-old age group, who are between the third and fifth year of elementary school and who have already started the literacy process in Portuguese and English. As a result of this research, we present our own prototype activities that are produced in an online platform, of easy and free access, and that seek interaction when dealing with Phonological Awareness in its different levels, which develop at specific moments in the child's language maturation: awareness at the syllable level, at the intrasyllabic level, and at the phoneme level. Thus, we will explore the issue of Phonological Awareness as of great importance for the successful development of reading and writing in an additional language, considering that reflection on the functioning of the sounds of the mother tongue may help in the development of the phonological system of another, building distinctions, separations, and exclusive uses of sounds within the system of each one.